AB0523 Cutaneous Manifestations in Primary Sjogren's Syndrome. (15th July 2016) - Durigan, V.; Troitiño, C.; Duarte, V.; Secco, A.; Mamani, M.
Abstract : Background: Cutaneous manifestations are one of the most common extraglandular manifestations of Sjogren's syndrome (SS). Entities such as as Annular erythema, Sweet syndrome, erythema nodosum and vasculitis have been described. Vasculitis was reported in approximately 10% of SS patients, with histologically characterized by lymphocytic or leukocytoclastic vasculitis. Objectives: Describe cutaneous manifestations in patients with primary SS, registered in the GESSAR (Argentine Study Group for the Sjogren Sydrome) database and determine their association with systemic and laboratory clinical manifestations. Methods: Observational, analytical case-control study. Patients aged 18 years and older with a diagnosis of primary SS. Demographic, clinical and serological data about patients included in the GESSAR database was collected, from the moment of joining until June 2015. Cases (patients with cutaneous manifestations) and controls (patients without cutaneous manifestations) were included with a relationship 1:4. Cutaneous manifestations were described. In addition, patients with purple were compared to the rest of the patients included in the study. For the analysis of continuous variables t or Mann Whitney tests were used, according to distribution and sample size. Categorical variables were analyzed using chi-square or Fisher exact test, according to the expected frequency distribution table. Multivariate logistic regression analysis was performed. Results: 335 patients were included, 67 with cutaneous manifestations, with an average age of 53 years (SD 15). 95% are female and the average diagnosis age is 47 years (SD 17). In the group of patients who had cutaneous manifestations, 60% had purple, 19% urticaria, 19% petechiae, 16% ulcers, 7% erythema multiforme, 4% erythema nodosum and 9% subcutaneous nodules. No statistically significant differences in age, sex and time of evolution of the disease between the two groups were found. In univariate analysis differences were found in: arthritis (47% vs 31%, p=0.01), neuropathy (21% vs 9%, p<0.01), decrease in C4 levels (34% vs 18%, p<0.01), decrease in C3 levels (25% vs 10%, p<0.01) and positive cryoglobulins (27% vs 9%, p<0.01). In the multivariate analysis no independent association of these variables was found. With respect to purple, significant differences were found with: arthritis (49% vs 31%, p=0.02), neuropathy (9% vs 25%, p<0.01), anemia of chronic disorders (34% vs 17%, p<0.01), decreased C3 (37% vs 10%, p<0.01) decrease in C4 level (49% vs 15%, p<0.01), anti LA (66% vs 47%, p<0.03) and positive cryoglobulins (37% vs 10%, p<0.01). In multivariate analysis, the decrease in C4 levels (OR 4.5; 95% CI 1.6–12.9, p<0.05) and positive cryoglobulins (OR 5.6; 95% CI 1.7–18.6, p<0.05) were independently associated with the presence purple. Conclusions: No independent associations were found regarding demographic, clinical and serological characteristics between patients with and without cutaneous manifestations. Purple is the most common cutaneous manifestation. The group of patients with Purple is most often associated with decreased C4 levels and the presence of cryoglobulins. References: Pilar Brito-Zer. Evoluciόn y pronόstico del paciente con Síndrome de Sjögren Primario. M Ramos-Casals, Primary Sjögren's syndrome: new clinical and therapeutic concepts. Manuel Ramos-Casals, Roser Solans, MD, Ph, Jose Rosas Primary Sjogren Syndrome. Disclosure of Interest: None declared